El dispositivo venezolano de sanidad y la incorporación de los médicos exiliados de la Guerra Civil española The Venezuelan sanitation authority and the incorporation of physicians exiled from the Spanish Civil War - Juan José Martin-Frechilla (História, Ciências, Saúde: Manguinhos, 2008)
En 1914, mientras España establecía acuerdos para modernizar su estructura científica y sanitaria, al hilo del panamericanismo y de los controles por la apertura del Canal de Panamá, Venezuela comenzó a estructurar un dispositivo sanitario ajustado a pautas internacionales, auspiciado, desde 1913, por la Fundación Rockefeller. En 1931, la Segunda República aceleró en España el envío de becarios a Estados Unidos y creó un sistema de salud pública bajo el modelo administrativo de unidades sanitarias y unidades técnicas de investigación y control propugnado por la Fundación. La Guerra Civil interrumpió ese proceso y Venezuela aprovechó el momento para contratar a médicos y enfermeras exiliados y los incorporó al nuevo Ministerio de Sanidad y Asistencia Social creado 1936. In 1914, while Spain was making agreements to modernize its scientific and sanitary structure, Venezuela started to structure a sanitation authority following international models, in line with Pan Americanism and the controls for the opening of the Panama Canal, for which is received sponsorship from the Rockefeller Foundation as of 1913. In 1931, the Second Spanish Republic sent ever greater numbers of scholars to study in the United States and established a public health system along the lines of the administrative models for sanitation and technical units for investigation and control as proposed by the Foundation. The Spanish Civil War interrupted this process and Venezuela seized the moment to hire the exiled doctors and nurses and incorporate them into its new Ministry for Sanitation and Social Welfare, created in 1936.